Antitumor immunostimulatory activity of the traditional Chinese medicine polysaccharide on hepatocellular carcinoma - Liu, Yang; Wu, Jiawen; Hao, Huiqin (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) is a prevalent malignancy, often associated with compromised immune function in affected patients. This can be attributed to the secretion of specific factors by liver cancer cells, which hinder the immune response and lead to a state of immune suppression. Polysaccharides derived from traditional Chinese medicine (TCM) are valuable constituents known for their immunomodulatory properties. This review aims to look into the immunomodulatory effects of TCM polysaccharides on HCC. The immunomodulatory effects of TCM polysaccharides are primarily manifested through the activation of effector T lymphocytes, dendritic cells, NK cells, and macrophages against hepatocellular carcinoma (HCC) both in vivo and in vitro settings. Furthermore, TCM polysaccharides have demonstrated remarkable adjuvant antitumor immunomodulatory effects on HCC in clinical settings. Therefore, the utilization of TCM polysaccharides holds promising potential for the development of novel therapeutic agents or adjuvants with advantageous immunomodulatory properties for HCC.